Decrease Levels of Chromium, Copper, and Nickel in Liquid Waste of The Electroplating Laboratory of Medan Polytechnic with Electrocoagulation Method - Alva, Sagir (Journal of Chemical Natural Resources, 2021)
The liquid waste contained several metals such as Cr, Cu, and Ni in concentrations of 64 mg / L, 252 mg / L, and 125 mg / L, which may cause environmental pollution. The process of coating metal has resulted in heavy metal waste. The electrocoagulation process is a combination between electrochemical processes and coagulation-flocculation processes. This research aims to use the electrocoagulation method as an alternative for treating wastewater containing heavy metals in particular. The results showed a decreasing trend of percentage in metal content with decreased levels of 99.931%, 99.837%, and 99.994% for Cr, Cu, and Ni, respectively.